2022
DOI: 10.1007/s00248-021-01952-z
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Microbial Profiling of Arabian Sea Oxygen Minimal Zone Reveals Complex Bacterial Communities and Distinct Functional Implications

Abstract: Arabian Sea harbours one of the largest oxygen minimal zones (OMZs) among the global oceans wherein biogeochemical cycles are regulated through dominant and complex microbial processes. The present study investigated the bacterial communities at various depths of the Arabian Sea OMZ using high-throughput sequencing of the v3-v4 hyper variable region of 16S rRNA gene. A total of 10 samples which included water samples from 8 different depths and 2 sediment samples were analyzed in this study. About 2.7 million … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…As a result, investigation of the microbial community structure and function in the NIO is significant to the potential expansion of OMZs and assess the effects of expanding OMZs to ecosystem health and climate change (Beman et al, 2021). Previous studies documented that the microbial community structure of OMZs varied with changes in organic carbon availability, DO concentration, and water depth (Cavan et al, 2017;Aldunate et al, 2018;Rangamaran et al, 2023). In this study, we investigated oceanic habitats with different levels of DO, and found that the bacterial community in the NIO varied with DO and water depth.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…As a result, investigation of the microbial community structure and function in the NIO is significant to the potential expansion of OMZs and assess the effects of expanding OMZs to ecosystem health and climate change (Beman et al, 2021). Previous studies documented that the microbial community structure of OMZs varied with changes in organic carbon availability, DO concentration, and water depth (Cavan et al, 2017;Aldunate et al, 2018;Rangamaran et al, 2023). In this study, we investigated oceanic habitats with different levels of DO, and found that the bacterial community in the NIO varied with DO and water depth.…”
Section: Discussionmentioning
confidence: 69%
“…OMZs contribute approximately 30-50% of the total nitrogen loss from oceans (Gruber and Sarmiento, 1997;Codispoti et al, 2000) via anaerobic ammonium oxidation (also known as anammox) (Kuypers et al, 2005;Hamersley et al, 2007) and denitrification (Jayakumar et al, 2004;Castro-Gonzaĺez et al, 2005). Furthermore, nitrogen loss causes nutrient limitation and reduced photosynthesis in the oceans (Gruber and Sarmiento, 1997;Codispoti et al, 2000;Lam and Kuypers, 2011;Rangamaran et al, 2023). OMZs also contribute to climate change (e.g., global warming) directly as they are large sources of carbon dioxide, nitrous oxide, and other greenhouse gases (Paulmier et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent reports have highlighted the prevalence of Proteobacteria as the dominant phylum among the microbial communities across the Indian Ocean. Other taxa at class level including the Betaproteobacteria, Deltaproteobacteria, Actinobacteria, Nitrospinia, Planctomycetacia, and SAR406 were also reported, although their relative abundance varied along the depths and locations sampled in the Indian Ocean OMZ (Bandekar et al, 2018;Fernandes et al, 2020;Jin et al, 2022;Li et al, 2022;Rangamaran et al, 2022). Although Proteobacteria predominates in the water column, significant change in the composition of the bacterial community was observed and varied with depth and DO levels in the water and sediment samples in the Arabian Sea (Rangamaran et al, 2022).…”
Section: Introductionmentioning
confidence: 95%
“…Other taxa at class level including the Betaproteobacteria, Deltaproteobacteria, Actinobacteria, Nitrospinia, Planctomycetacia, and SAR406 were also reported, although their relative abundance varied along the depths and locations sampled in the Indian Ocean OMZ (Bandekar et al, 2018;Fernandes et al, 2020;Jin et al, 2022;Li et al, 2022;Rangamaran et al, 2022). Although Proteobacteria predominates in the water column, significant change in the composition of the bacterial community was observed and varied with depth and DO levels in the water and sediment samples in the Arabian Sea (Rangamaran et al, 2022). Previous reports based on clone libraries revealed the vertical partitioning of bacterial communities between the surface and OMZ at the Arabian Sea Time Series (ASTS) location, however no apparent seasonal variation among OMZ bacterial communities (Bandekar et al, 2016(Bandekar et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%